2018
DOI: 10.1038/s41929-018-0178-2
|View full text |Cite
|
Sign up to set email alerts
|

A vitamin K-dependent carboxylase orthologue is involved in antibiotic biosynthesis

Abstract: alonomycin (antibiotic K16) 1 (Fig. 1a) is a secondary metabolite with antiprotozoal and antifungal activity, isolated from Streptomyces rimosus paromomycinus 1. Malonomycin is the only known bacterial natural product with an intact aminomalonic acid moiety. While the structure of malonomycin was established some time ago, with l-Ser and l-diaminopropionate (l-Dap) as probable precursors 1-3 , the biosynthetic pathway, including the origin of the unique aminomalonate unit, has remained unexplained. Malonates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“… 192 , 198 The elimination of bacterial virulence factors carried on virulence plasmids and resistance determinants in commensal bacteria has been carried out by the CRISPR/Cas9 “pro-active” genetic system (Pro-AG), a recently developed system. 192 , 199 The enhanced cytotoxic potential is associated with the intentional or accidental targeting of the sequence of bacterial genome by Cas9 nuclease, 200 leading to apoptosis because of the introduction of irreversible chromosomal lesions. 201 , 202 Therefore, a CRISPR-guided RNA can be fabricated to exclusively target resistance or virulence genes, reverting to antibiotic susceptible ones by inducing a break inside the dsDNA of resistant bacteria.…”
Section: The Way Forward: Protecting Global Healthmentioning
confidence: 99%
“… 192 , 198 The elimination of bacterial virulence factors carried on virulence plasmids and resistance determinants in commensal bacteria has been carried out by the CRISPR/Cas9 “pro-active” genetic system (Pro-AG), a recently developed system. 192 , 199 The enhanced cytotoxic potential is associated with the intentional or accidental targeting of the sequence of bacterial genome by Cas9 nuclease, 200 leading to apoptosis because of the introduction of irreversible chromosomal lesions. 201 , 202 Therefore, a CRISPR-guided RNA can be fabricated to exclusively target resistance or virulence genes, reverting to antibiotic susceptible ones by inducing a break inside the dsDNA of resistant bacteria.…”
Section: The Way Forward: Protecting Global Healthmentioning
confidence: 99%
“…Aminomalonate (Ama), the structural congener of aspartate and glutamate,isalong known metabolite in Nature and was proposed to be an intermediate in glycine biosynthesis. [1,2] Ama has been found in several natural products, [3][4][5][6][7] and can also serve as an extender unit in the biosynthesis of polyketides and/or non-ribosomal peptides (Figure S1). [8][9][10][11] Ama was also found as an important constituent in the Escherichia coli (E. coli)p rotein hydrolysate,a nd is likely widespread in various proteomes.…”
Section: Introductionmentioning
confidence: 99%
“…8 Such a process is not dissimilar to the biosynthesis of tetramate natural products. 9,10 We have also shown that allo -arylserines 1f close by the conventional route A pathway 5 to give tetramate 4e via the Dieckmann cyclisation of the major malonamide diastereomer 2g , but interestingly, the minor 2,5- trans malonamide 2e diastereomer derived from threo -aryl serines 1e has been found to ring close by route B to give tetramate 5e . The exclusive chemoselective formation of tetramates 4e and 5e can be explained via steric effects, in which the bulky C2- t -Bu and C4-aryl groups prefer to reside on the less hindered exo -face of the bicyclic lactam.…”
Section: Introductionmentioning
confidence: 81%